A handbook of nuclear applications in humans' lives - Tabbakh, Farshid (Cambridge Scholars, 2020)
Without using nuclear technology, today's societies would not be as developed as they are. Increasing public knowledge about the countless advantages of this technology not only improves people's health, but also it significantly provides economic growth for the whole society. This handbook provides a full, comprehensive introduction to the applications of nuclear technology. It details the usage of nuclear technology in every aspect of life, including in various different industries, medicine and health, art and cultural heritage, and security and forensics.